Immunological Network in Head and Neck Squamous Cell Carcinoma—A Prognostic Tool Beyond HPV Status - Fialová, Anna; Koucký, Vladimír; Hajdušková, Martina; Hladíková, Kamila; Špíšek, Radek (Frontiers in Oncology, 2020)
Head and neck squamous cell carcinoma (HNSCC) is a highly heterogeneous disease that affects more than 800 000 patients worldwide each year. The variability of HNSCC is associated with the differences in the carcinogenesis processes that are caused by two major etiological agents, namely, alcohol/tobacco and human papillomavirus (HPV). Compared to nonvirally induced carcinomas, the oropharyngeal tumors associated with HPV infection show markedly better clinical outcomes and are characterized by an immunologically "hot" landscape with high levels of tumor-infiltrating lymphocytes. However, the standard of care remains the same for both HPV-positive and HPV-negative HNSCC. Surprisingly, treatment de-escalation trials have not shown any clinical benefit in patients with HPV-positive tumors to date, most likely due to insufficient patient stratification. The in-depth analysis of the immune response, which places an emphasis on tumor-infiltrating immune cells, is a widely accepted prognostic tool that might significantly improve both the stratification of HNSCC patients in de-escalation trials and the development of novel immunotherapeutic approaches.